2007
DOI: 10.1557/proc-1054-ff06-05
|View full text |Cite
|
Sign up to set email alerts
|

Self-Organization and Nanocluster Formation Processes in Nonlinear Molecular Chains

Abstract: The goal of this work is to investigate self-organization processes in molecular chains. Computer simulation has been performed by means of a molecular dynamics method. Morse potential was chosen as the potential of atomic interaction. Molecular chains were exposed to low-energy ion impact by two means: mono beam and plasma treatment. The amount of the energy transferred to molecules of the chain was varied in a wide range but it must be less than the energy needed to break the chain.We showed that nonlinear o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Previous tests revealed that interaction between charged particles of the plasma beam and the radiated surface of a crystalline material rearranges the crystal lattice of a material subjected to treatment [6]. The bombarding of the solid surface with the low-energy ion beam excites the oscillation of the atoms of the crystal lattice and makes it move deep inside the material [7]. The induced displacement of vacancies and dislocations is similar to the mechanism connected with the relaxation of stresses during heat treatment.…”
Section: Introductionmentioning
confidence: 92%
“…Previous tests revealed that interaction between charged particles of the plasma beam and the radiated surface of a crystalline material rearranges the crystal lattice of a material subjected to treatment [6]. The bombarding of the solid surface with the low-energy ion beam excites the oscillation of the atoms of the crystal lattice and makes it move deep inside the material [7]. The induced displacement of vacancies and dislocations is similar to the mechanism connected with the relaxation of stresses during heat treatment.…”
Section: Introductionmentioning
confidence: 92%